(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Public relations represent the interactions of state agencies and enterprises with citizens, public organizations, political parties, self-governance bodies, and various segments of the population aimed at jointly addressing social issues. These actions are directed toward ensuring legality in society.